Kebijakan Fiskal Pada Masa Utsman Bin Affan - Salman Zakki Syahriel Mubarok; Slamet Santoso (CV. ULIL ALBAB CORP, 2022)
This paper discusses Uthman bin Affan's fiscal policy descriptively. Caliph Uthman bin Affan was the third caliph after the Khulafaur Rashidun era. Fiscal policy is a policy carried out in managing state revenues and revenues. Uthman's concept of fiscal policy is a concept based on sharia principles that aims to benefit the people. Uthman bin Affan's fiscal policy was to regulate zakat, kharaj, jizyah and usyur. This third caliph has succeeded in implementing fiscal policy in running the economy and can be used as a reference by regulating the economy of our country